ANALISIS PREDIKSI FINANCIAL DISTRESS DENGAN MENGGUNAKAN MODEL ALTMAN Z-SCORE PADA UMKM DI PAMEKASAN - Romaniyah; Nurul Alfian (Faculty of Economics and Business, Universitas Warmadewa, 2024)
Fraud is related to the bankruptcy of a company. Management will be motivated to commit fraudulent financial statements when they know that the company being managed is experiencing financial distress.. The purpose of this study is to predict the bankruptcy of MSMEs by using the Altman Z-Score Model to predict. The population in this study is the financial statements of all MSMEs in Pamekasan.samples taken from the population must be truly representative. Registered MSMEs that match the criteria made are samples in this study. The sampling technique used is purposive sampling. The results of the Altman Z-Score Model research are able to predict the financial condition of MSMEs that are sampled in this study. In 2021, there are 7 MSMEs that are predicted to be safe, 5 MSMEs are in a gray position, and 3 MSMEs are predicted to go bankrupt. In 2021, from a total sample of 15 MSMEs, there were 12 MSMEs that did not commit fraud or fraud, this shows that the company has been able to present financial statements without making stakeholders make wrong decisions, meaning that the company does not prioritize their personal benefits but conveys them truthfully. The measurement of the two variables, namely the Modified Almant Z-Score model and the F-Score model, can then be linked to whether there are companies that are predicted to fall into the category of danger zone (distress finance), which are potentially likely to commit financial statement fraud (fraudulent). In 2021, it shows that MSME company with code UPS, FCS dan UTPD is also in the danger zone and is an indication of the possibility of committing financial statement fraud (fraudulent). Key Words: Financial Distress, Altman Z-Score, MSMEs